2021
DOI: 10.1021/acs.nanolett.1c00014
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Trap Dynamics in a CsPbBr3 Single-Crystal Microplate by Ultrafast Photoemission Electron Microscopy

Abstract: For versatile lead-halide perovskite materials, their trap states, both in the bulk and at the surface, significantly influence optoelectronic behaviors and the performance of the materials and devices. Direct observation of the trap dynamics at the nanoscale is necessary to understand and improve the device design. In this report, we combined the femtosecond pump–probe technique and photoemission electron microscopy (PEEM) to investigate the trap states of an inorganic perovskite CsPbBr3 single-crystal microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Each time, the sample is heated to the given temperature via a filament installed in the sample holder and then left to cool down to room temperature prior to the measurement. As shown in Figure e, there is a significant rise of PE after annealing at temperatures higher than 600 K. This results from the depletion of lattice oxygen in NiO, according to previous reports. , It has been revealed that the defect density at the TMO surface is much higher than that at the bulk, and these defects would significantly affect the electron behaviors around the surface. , As shown in Figure f,g, after the UHV annealing, τ 1 decreases from 0.86 to 0.56 ps, while τ 2 increases to 0.49 ps. Since oxygen vacancies in NiO are located deeply in the band gap, they are expected to act as trap states, causing the relaxation of excited electrons at higher energy levels.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Each time, the sample is heated to the given temperature via a filament installed in the sample holder and then left to cool down to room temperature prior to the measurement. As shown in Figure e, there is a significant rise of PE after annealing at temperatures higher than 600 K. This results from the depletion of lattice oxygen in NiO, according to previous reports. , It has been revealed that the defect density at the TMO surface is much higher than that at the bulk, and these defects would significantly affect the electron behaviors around the surface. , As shown in Figure f,g, after the UHV annealing, τ 1 decreases from 0.86 to 0.56 ps, while τ 2 increases to 0.49 ps. Since oxygen vacancies in NiO are located deeply in the band gap, they are expected to act as trap states, causing the relaxation of excited electrons at higher energy levels.…”
Section: Resultssupporting
confidence: 79%
“…In this paper, we exploit the advantages of a recently established equipment, laser-excited photoemission electron microscopy (PEEM), to investigate the bilateral electron transferring process in the GDY/TMO heterostructure. Under the incidence of visible-ranged laser beam, the photoexcited electrons are collected and filtered by a hemisphere energy analyzer, providing simultaneous spatial and energy resolution with a highly selective focus on the electron behaviors near the Fermi level. The adaption of ultrafast pump–probe laser beam pulses allows us to trace the motion of electrons at the scale of femtoseconds. , We discover that the induction of point defects would have different influences on the two directions of charge transferring process, depending on the location of the defects. A heterostructure for a practical device based on a three-dimensional supporting substrate is also investigated, where spatial inhomogeneity is found to be a major stumbling block for the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is compatible with conclusions from other stud-ies. 25 The mean bulk non-radiative rate is (1.0 ± 0.1) × 10 8 s −1 , which is much faster than the mean radiative rate of (5 ± 1) × 10 6 s −1 . Therefore, non-radiative effects dominate the carrier dynamics, as predicted by previous studies.…”
Section: Model Resultsmentioning
confidence: 85%
“…These carriers can then diffuse throughout the NW and may re-combine radiatively: alternatively the carriers may be trapped and recombine non-radiatively at the top interface or in the bulk. 23,25 Transmission electron microscopy measurements do not observe the formation of any strain-related defects at the bottom interface, 18 and the TCSPC measurements also show no evidence of an additional recombination mechanism.…”
Section: Model Resultsmentioning
confidence: 98%
See 1 more Smart Citation